In pursuit of recognition and the expression of power?: making sense of vulgarity in Zimdancehall - Parwaringira, Blessed; Mpofu, Phillip (Routledge, 2022)
While there are many refined musical productions, Zimdancehall is epitomised by the use of explicit vulgar lyrics. This article attempts to make sense of vulgarity in the musical genre against the knowledge that, although vulgarity is obnoxious in the public sphere, it is functional in specific contexts among the Shona people of Zimbabwe. Deploying a theoretical gaze that is grounded in concepts of indigenous knowledge systems, aesthetics of vulgarity and subalternity, the article grapples with Zimdancehall artists’ pursuit of creative power and recognition through unorthodox use of vulgar lyrics. The article shows the expediency of vulgarity in artists’ expressions of power, and how it is used to gain fame in a highly competitive music industry with established musicians. Such artistic power is gained through the “diss” modus, that is, through the appropriation of masculine supremacy and the subversion of femininity. Counter-hegemonic discourses are used to contest the dominance of rival artists by employing vulgar humour. It is one thing to pursue recognition, but it is another to be recognised. The use of vulgar lyrics alone does not always translate into artistic power and fame.